Efektivitas Media Kartu Visual terhadap Peningkatan Kosakata Literasi Dasar Siswa Kelas Rendah: Sebuah Studi Literatur (Periode 2022-2026) - Komariah, Komariah; Sumartiningsih, Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Background: The low mastery of basic literacy vocabulary among Phase A students (1st Grade) represents a critical challenge during the preschool transition period. This transition frequently encounters cognitive obstacles that necessitate immediate solutions. The Magical Flash Card media emerges as an innovation to address basic literacy limitations through a concrete approach. Objective: This study aims to analyze the effectiveness of visual card media, specifically the "Magical Flash Card," in enhancing vocabulary acquisition through a systematic literature review. Methods: This research employed the Systematic Literature Review (SLR) method, analyzing 30 primary scientific articles published between 2022 and 2026 from SINTA, Google Scholar, and ERIC databases. Results: Data synthesis indicates that visual card media consistently improves visual word recognition through dual coding and spaced repetition mechanisms. Comparative analysis reveals that despite variations in effectiveness, the use of "Magical Flash Card" yielded an average Normalized Gain (N-Gain) score of 0.41, categorized as "Moderate," reflecting reliable and stable learning progress. Conclusion: Visual card media is proven to be an effective and adaptive cognitive scaffold for the Merdeka Curriculum through joyful, mindful, and meaningful learning approaches, thereby stimulating students' thinking skills more rapidly. The implications of this study emphasize the importance of collaborative concrete media innovation to overcome time constraints and sample limitations in elementary school literacy instruction. Visual card media, particularly the Magical Flash Card innovation, serves as a highly recommended pedagogical instrument for strengthening Phase A basic literacy. Further research is suggested to expand the sample scale and integrate more explorative media design variations